Unconventional endosome-like compartment and retromer complex in Toxoplasma gondii govern parasite integrity and host infection - Lamba Omar Sangaré (Nature Portfolio, 2016)
The retromer complex is a multi-protein component of the endosomal protein sorting machinery. Here, Sangaré et al. identify unique features in the retromer complex of the parasite Toxoplasma gondii, and show that it is crucial for the biogenesis of secretory organelles in this pathogen.